2022
DOI: 10.3390/plants11202769
|View full text |Cite
|
Sign up to set email alerts
|

Salt Tolerant Bacillus Strains Improve Plant Growth Traits and Regulation of Phytohormones in Wheat under Salinity Stress

Abstract: Soil salinity is a major constraint adversely affecting agricultural crops including wheat worldwide. The use of plant growth promoting rhizobacteria (PGPR) to alleviate salt stress in crops has attracted the focus of many researchers due to its safe and eco-friendly nature. The current study aimed to study the genetic potential of high halophilic Bacillus strains, isolated from the rhizosphere in the extreme environment of the Qinghai–Tibetan plateau region of China, to reduce salt stress in wheat plants. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 67 publications
(88 reference statements)
4
10
0
Order By: Relevance
“…Additionally, compared to the control, PDC (38.5%), BDH (41.5%), 1,2-BIT (42.0%), and MIX-VOCs (58.2%) all considerably reduced the activity of MDA. Similar findings were reported by Liang et al (2022) and Ayaz et al (2022), who found that in circumstances of VOC stress, antioxidant enzymes were greatly enhanced and MDA concentration dramatically decreased with the use of Bacillus and synthetic VOCs (Ayaz et al 2021;Liang et al 2022).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, compared to the control, PDC (38.5%), BDH (41.5%), 1,2-BIT (42.0%), and MIX-VOCs (58.2%) all considerably reduced the activity of MDA. Similar findings were reported by Liang et al (2022) and Ayaz et al (2022), who found that in circumstances of VOC stress, antioxidant enzymes were greatly enhanced and MDA concentration dramatically decreased with the use of Bacillus and synthetic VOCs (Ayaz et al 2021;Liang et al 2022).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the cell shrinks due to the evacuation of its cytoplasmic contents and the disappearance of its cytoplasmic organelles. (43.5,39.7,46.5,and 51.1%) and POD (23.5,21.1,24.4,and 25.9%), respectively, as compared to control, which agrees with (Ayaz et al 2022). The activities of CAT (26.2,28.6,29.5,and 33.5%),APX (39.4,37.8,39.5,and 42.5%), and H 2 O 2 (38.4, 41.5, 45.4, and 51.0%) were similar to those of control according to earlier research (Ali et al 2022a).…”
Section: Discussionsupporting
confidence: 88%
“…Application of both inoculants significantly downregulated the expression of ABA- response element ( ABARE ), 4-Hydroxy-2-nonenal ( 4-HNE ), whereas the P5CS gene was found to be upregulated. This clearly illustrates that these halophilic microbes regulate key stress signaling pathways (ABA synthesis, MDA and proline production) that subsequently lowered the effect of stress ( Ayaz et al., 2022 ). From the cited literature ( Table 1 ), it is evident that PGPR could alleviate salt stress by improving soil health, nutrient uptake, hormone production, antioxidant activity, and stress- responsive genes.…”
Section: Role Of Pgpr-based Biostimulants In Combating Abiotic Stressmentioning
confidence: 92%
“…PGPR traits; antagonistic bacteria; Tritium aestivum; 16s rRNA 2 Wheat (Triticum aestivum) is grown in 17% of farmland globally and provides about 82% of the protein source and 80% of the calories for the global population [2][3][4]. It is grown annually on around 220 million hectares area and approximately 775 metric tons of yield is reported in the world per year [5].…”
Section: Abstract Endophytes;mentioning
confidence: 99%